НОВІ ЗНАХІДКИ РІДКІСНИХ ТВЕРДОКРИЛИХ У МЕЖАХ РІВНИННОЇ ЧАСТИНИ ПРАВОБЕРЕЖНОЇ УКРАЇНИ. І. ТУРУНИ (COLEOPTERA: CARABIDAE) - Nazarov, N. V.; Martynov, A. V.; Kavurka, V. V. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2022)
Data on new records of 15 species of ground beetles from the lowland part of Right-bank Ukraine are provided (namely Leistus rufomarginatus (Duftschmidt, 1812), Blethisa multipunctata (Linnaeus, 1758), Ophonus sabulicola (Panzer, 1796), Acupalpus brunnipes (Sturm, 1825), Stenolophus proximus Dejean, 1829, S. skrimshiranus Stephens, 1828, Dromius quadrimaculatus (Linnaeus, 1758), Microlestes maurus (Sturm, 1827), Agonum angustatum Dejean, 1828, A. duftschmidi J. Schmidt, 1994, A. emarginatum (Gyllenhal, 1827), A. longicorne Chaudoir, 1846, Paranchus albipes (Fabricius, 1796), Platynus livens (Gyllenhal, 1810), Pterostichus quadrifoveolatus Letzner, 1852). Leistus rufomarginatus (Duftschmidt, 1812) is reported from Zhytomyr Region for the first time; Stenolophus skrimshiranus Stephens, 1828 is first registered within Right-bank Polissya.